2018
DOI: 10.1590/0103-8478cr20170375
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two artificial diets to rear Elaphria agrotina

Abstract: Given the increasing importance of Elaphria agrotina (Guenée) (Lepidoptera: Noctuidae) in corn crops, especially in the Brazilian Savannah biome, the present research aimed to study its development and survival on Greene’s and Poitout & Bues’s artificial diets (25±1°C, 70±10% relative humidity [RH] and 12h photophase). Poitout & Bues’s diet was more suitable than Greene’s diet, providing higher survival percent (77.51% vs. 5.57%), lower development time (49.81 days vs. 55.24 days) and higher fecundity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…The survival of 89% of individualised larvae maintained in the artificial diet may indicate that even if there is a preference for grasses in the field (see the hostplant topic below), in the absence of these plants, the larvae can develop on alternative foods, such as plants from other families, fruits and artificial diets. Even though it is known that other noctuids develop better on diets based on grasses such as corn (Otanásio et al 2018; Poitout & Buer 1974), the survival percentage found in this study is higher than that considered adequate (75%) for the establishment and maintenance of insect colonies in the laboratory (Schneider 2009; Singh 1983).…”
Section: Discussioncontrasting
confidence: 66%
“…The survival of 89% of individualised larvae maintained in the artificial diet may indicate that even if there is a preference for grasses in the field (see the hostplant topic below), in the absence of these plants, the larvae can develop on alternative foods, such as plants from other families, fruits and artificial diets. Even though it is known that other noctuids develop better on diets based on grasses such as corn (Otanásio et al 2018; Poitout & Buer 1974), the survival percentage found in this study is higher than that considered adequate (75%) for the establishment and maintenance of insect colonies in the laboratory (Schneider 2009; Singh 1983).…”
Section: Discussioncontrasting
confidence: 66%